2019
DOI: 10.1186/s12885-019-5788-9
|View full text |Cite
|
Sign up to set email alerts
|

Two open-label, single arm, non-randomized phase II studies of irinotecan for the treatment of metastatic breast cancer in patients with increased copy number of the topoisomerase I gene

Abstract: Background Treatment options in metastatic breast cancer are limited. New therapies preferable with predictive biomarkers are needed. The aim of these trials was to investigate if gene copy number of the topoisomerase 1 gene was predictive of response to the topoisomerase inhibitor irinotecan. Methods Two open-label, single-arm phase II studies including HER2 positive and negative patients were conducted. Patients were eligible for inclusion if the primary tumor or a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Given the dose-limiting toxicity of irinotecan and its inactivity in a large proportion of patients, it is more desirable to identify a biomarker to predict irinotecan’s activity. Some researchers have explored whether the increased topoisomerase 1 gene copy number or UGT1A1 polymorphisms can predict the response of the topoisomerase inhibitor irinotecan ( 3 , 12 ). Due to the limited number of cases, no significant correlation has been found to be related to irinotecan’s response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the dose-limiting toxicity of irinotecan and its inactivity in a large proportion of patients, it is more desirable to identify a biomarker to predict irinotecan’s activity. Some researchers have explored whether the increased topoisomerase 1 gene copy number or UGT1A1 polymorphisms can predict the response of the topoisomerase inhibitor irinotecan ( 3 , 12 ). Due to the limited number of cases, no significant correlation has been found to be related to irinotecan’s response.…”
Section: Discussionmentioning
confidence: 99%
“…A few clinical trials have shown that irinotecan had modest systemic activity in some patients previously treated with anthracyclines and taxanes. The objective response rate (ORR) of patients with MBC who received irinotecan monotherapy was 5%–23%, while the ORR of patients with MBC who received a combination of irinotecan and various chemotherapy drugs ranged from 14%–64%, usually including patients who had been heavily pretreated ( 5 , 12 , 13 ). Irinotecan has not been regarded as a routine treatment option for patients with MBC, and the outcome of subsequent therapy with irinotecan in patients with MBC was not clear.…”
Section: Introductionmentioning
confidence: 99%